TEACHERS’ TRAINING SKILLS & STUDENTS’ PERFORMANCE IN ACADEMIC COMPETITIONS - Yang, Lirui (Pacific International Journal, 2024)
In the ever-evolving landscape of higher education, the symbiotic relationship between effective teaching methodologies and students’ academic achievements has garnered considerable attention. This study explores the intricate nexus between teachers’ training skills and students’ performance in academic competitions, focusing on Hubei University of Science and Technology(HUST). As a beacon of academic excellence, HUST’s participation and success in the ’Internet+’ Innovation and Entrepreneurship Competition provide a unique context for investigation. The central research problem delves into understanding the dynamics between teachers’ training skills and students’ performance, emphasizing the specific context of innovation and entrepreneurship within the ’Internet+’ competition. The study scrutinizes whether educators at HUST significantly influence their students’ success in academic competitions, particularly those demanding a synthesis of technical skills, innovation, and entrepreneurial acumen. Contributing nuanced insights to the well-established link between quality teaching and student success, this study aims to unravel specific skills and pedagogical approaches beneficial in the context of academic competitions. Additionally, the research explores how teachers contribute to shaping students’ innovation and entrepreneurial mindset, crucial in the contemporary, technology-driven economy. With a twofold purpose, the study empirically examines the relationship between teachers’ training skills and students’ success in academic competitions while elucidating the mechanisms through which teachers contribute to students’ innovation and entrepreneurial capabilities. Focusing on HUST, this research provides context-specific insights that extend beyond the university, contributing to the broader discourse on the interplay between teaching effectiveness and students’ achievements in academic competitions.